Transcriptome Approach Reveals the Response Mechanism of Heimia myrtifolia (Lythraceae, Myrtales) to Drought Stress - Lin, Lin; Wang, Jie; Wang, Qun; Ji, Mengcheng; Hong, Sidan; Shang, Linxue; Zhang, Guozhe; Zhao, Yu; Ma, Qingqing; Gu, Cuihua (Frontiers in Plant Science, 2022)
Drought is a major environmental condition that inhibits the development and cultivation of Heimia myrtifolia. The molecular processes of drought resistance in H. myrtifolia remain unknown, which has limited its application. In our study, transcriptome analyzes were compared across three treatment groups (CK, T1, and T2), to investigate the molecular mechanism of drought resistance. Plant leaves wilted and drooped as the duration of drought stress increased. The relative water content of the leaves declined dramatically, and relative electrolyte leakage rose progressively. Using an RNA-Seq approach, a total of 62,015 unigenes with an average length of 1730 bp were found, with 86.61% of them annotated to seven databases, and 14,272 differentially expressed genes (DEGs) were identified in drought stress. GO and KEGG enrichment analyzes of the DEGs revealed significantly enriched KEGG pathways, including photosynthesis, photosynthetic antenna proteins, plant hormone signal transduction, glutathione metabolism, and ascorbate and aldarate metabolism. Abscisic acid signal transduction was the most prevalent in the plant hormone signal transduction pathway, and other plant hormone signal transductions were also involved in the drought stress response. The transcription factors (including MYB, NAC, WRKY, and bHLH) and related differential genes on significantly enriched pathways all played important roles in the drought process, such as photosynthesis-related genes and antioxidant enzyme genes. In conclusion, this study will provide several genetic resources for further investigation of the molecular processes that will be beneficial to H. myrtifolia cultivation and breeding.